Treatment of Diabetes Mellitus Using iPS Cells and Spice Polyphenols - Qi Ge; Liang Chen; Keping Chen (Journal of Diabetes Research)
Diabetes mellitus is a chronic disease that threatens human health. The disease is caused by a metabolic disorder of the endocrine system, and long-term illness can lead to tissue and organ damage to the cardiovascular, endocrine, nervous, and urinary systems. Currently, the disease prevalence is 11.4%, the treatment rate is 48.2%, and the mortality rate is 2.7% worldwide. Comprehensive and effective control of diabetes, as well as the use of insulin, requires further study to develop additional treatment options. Here, we reviewed the current reprogramming of somatic cells using specific factors to induced pluripotent stem (iPS) cells capable of repairing islet β cell damage in diabetes patients to treat patients with type 1 diabetes mellitus. We also discuss the shortcomings associated with clinical use of iPS cells. Additionally, certain polyphenols found in spices might improve glucose homeostasis and insulin resistance in diabetes patients, thereby constituting promising options for the treatment of type 2 diabetes.